2014
DOI: 10.1016/s1995-7645(14)60294-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment and antioxidant analysis of 22 date palm (Phoenix dactylifera) varieties growing in Sultanate of Oman

Abstract: The present finding helps in understanding the nutritional significance of different date varieties in Oman while the lesser known varieties can be improved through sustainable horticultural practices as a valuable product. The study further reveals that the consumption of these dates' fruits would exert several beneficial effects by virtue of their antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 22 publications
8
55
2
1
Order By: Relevance
“…The crude fiber content of date fruit varied between 1.71 to 2.77g/100g. The values were within the range (1.0-2.5g/100g) reported by Al-Harrasi et al (2014). Elsohaimy and Hafez (2010) reported a higher value of crude fiber (5.30 to 6.51 g/100g) whereas Sadiq et al (2013) reported lower value (0.50g/100g) of crude fiber content than the values obtained in present study.…”
Section: Results and Discussion Proximate Compositionsupporting
confidence: 81%
“…The crude fiber content of date fruit varied between 1.71 to 2.77g/100g. The values were within the range (1.0-2.5g/100g) reported by Al-Harrasi et al (2014). Elsohaimy and Hafez (2010) reported a higher value of crude fiber (5.30 to 6.51 g/100g) whereas Sadiq et al (2013) reported lower value (0.50g/100g) of crude fiber content than the values obtained in present study.…”
Section: Results and Discussion Proximate Compositionsupporting
confidence: 81%
“…In general, the chemical composition of both varieties was situated in the medium level of the range suggested by Mrabet et al (), El‐Sohaimy and Hafez (), Al‐Harrasi et al (), Mahmood, Anwar, Abbas Boyce, and Saari (), and Assirey () for dozen date cultivars from Tunisia, Egypt, Sultanate of Oman, Sudan, and KSA.…”
Section: Resultsmentioning
confidence: 59%
“…The date fruit is also an excellent source of potassium and high fiber content. Date pit constitutes 10 to 15% on an average mass of total date fruit (Al‐Harrasi et al, ). It contains 7.7%–12.5% oil on an average basis (Al‐Farsi & Lee, ).…”
Section: Introductionmentioning
confidence: 99%